Study of morpho-functional determinants and their role in selecting the emerging champion( 12-15) years in middle distance race- a field study for the bourdj athletics association clubs - madassi, lotfi; aboura, rabeh (sports creativity, 2025)
This study aimed to shed light on the process of selecting and directing young talents in middle distance races at the level of the state bordj bou arreridj by knowing the most important determinants on which coaches focus in the process of selecting and guiding young champions , in order to reach the identification of the most important aspects that coaches rely on practical ,and in order to reach the results of our research topic ,we followed in our research this descriptive approach to its suitability and the nature of the topic. As the study sample , it consisted of 20 coaches who are active within the bourdj league athletics association clubs and were chosen in the intentional way , the questionnaire was used as a means of collecting data the researcher reached the following results: the coaches reliance in the selection process is largely dependent on physical determinants and to a lesser degree on physiological determinants , while we found that trainers neglect physical measurements as a morphological determinants due to the ignorance of some and the lack of measurement tools for others